2001
DOI: 10.1038/414619a
|View full text |Cite
|
Sign up to set email alerts
|

Electrical control of spin coherence in semiconductor nanostructures

Abstract: The processing of quantum information based on the electron spin degree of freedom requires fast and coherent manipulation of local spins. One approach is to provide spatially selective tuning of the spin splitting--which depends on the g-factor--by using magnetic fields, but this requires their precise control at reduced length scales. Alternative proposals employ electrical gating and spin engineering in semiconductor heterostructures involving materials with different g-factors. Here we show that spin coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
245
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(249 citation statements)
references
References 19 publications
4
245
0
Order By: Relevance
“…Electrical control of isolated spins through their g-factors is highly desireable for implementation of quantum gate operations. To date, electrical control of g-factors has only been observed in ensembles of electrons in quantum wells by shifting the electron wavefunctions into different materials [10,11,12,13]. In this Letter we present a striking electric field resonance in the g-factor for molecular spin states confined to a single quantum dot molecule.…”
mentioning
confidence: 91%
“…Electrical control of isolated spins through their g-factors is highly desireable for implementation of quantum gate operations. To date, electrical control of g-factors has only been observed in ensembles of electrons in quantum wells by shifting the electron wavefunctions into different materials [10,11,12,13]. In this Letter we present a striking electric field resonance in the g-factor for molecular spin states confined to a single quantum dot molecule.…”
mentioning
confidence: 91%
“…In measurements on InAs-based two-dimensional electron systems, values from g * = −1 to g * = −13 have been found experimentally depending on magnetic field direction [18], quantum well width [15] and barrier composition [15,17] and gate tunability of g * has been demonstrated [17,19]. Investigations on self-assembled InAs QDs using magnetotunneling and capacitance spectroscopy have revealed anisotropic g-factors with values from +0.5 to +1.6 [20,21].…”
mentioning
confidence: 99%
“…It was further shown that changing the dot length L allows us to design QDs along a nanowire with different specific spin splittings in a constant magnetic field. Future development of graded heterostructures is expected to allow individual gate tunable spin splittings [13,19] in a series of dots along a nanowire, which makes nanowire QDs containing a single electron spin interesting systems for the realization of qubits.…”
mentioning
confidence: 99%
“…In the presence of an electric field the minimum of the confining potential may be displaced with the center of the well, whereas the implicitly of the envelope of the wave function is conserved. This particular property of the partially filled triangular well makes it suitable for the practical realization of the electronic devices based on the manipulation of the g-factor for spintronic application [8].…”
Section: Discussionmentioning
confidence: 99%